A phosphorus-containing cycloolefin copolymer and its preparation method and application
By copolymerizing reaction using metallocene catalysts and alkylaluminum promoters under low water oxygen conditions, phosphorus-containing cycloolefin copolymers with excellent flame retardancy and optical properties were prepared, which solved the problem of difficulty in taking into account both flame retardancy and optical properties in the prior art, and achieved the satisfaction of high-end application requirements.
Patent Information
- Application Number
- CN202411591037.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-08
AI Technical Summary
The prior art is difficult to improve the flame retardancy of cycloolefin copolymers while maintaining high optical properties, and cannot meet the needs of high-end applications.
By copolymerizing cycloolefins, comonomers A, comonomer B and α-olefins in a system with low water oxygen content, phosphorus-containing cycloolefin copolymers with excellent flame retardancy, heat resistance and light transmittance are prepared.
The flame retardant grade of cycloolefin copolymer has been improved to V2 and V1, while retaining its excellent optical properties, and is suitable for high-end optical fireproof materials and medical materials.
Smart Images

Figure SMS_6 
Figure QLYQS_1 
Figure QLYQS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer synthesis, in particular to a phosphorus-containing cycloolefin copolymer and a preparation method and application thereof. Background Art
[0002] Cyclic olefin copolymers (COC) refer to polyolefin materials with a cyclic structure in the main chain, which are generally prepared by addition copolymerization of cycloolefins and alpha olefins (usually ethylene). Cyclic olefin polymers and cycloolefin copolymers have the advantages of good optical transparency, low birefringence, extremely low dielectric constant, excellent heat resistance, chemical resistance, melt fluidity, and dimensional stability. They also have the good moisture barrier and low water absorption that cycloolefin polymer resins generally have, and are widely used in optical lenses, optical semiconductors, medical products and other fields.
[0003] However, the flame retardancy of traditional COC is still at the self-extinguishing level and cannot meet market demand. In order to enhance the flame retardancy of COC, a common method is to add flame retardants to COC materials.
[0004] At present, COC flame retardants commonly used in industry are mainly brominated flame retardants such as decabromodiphenyl ether, octabromodiphenyl ether, tetrabromobisphenol A, and bromine-containing carbonate polymers, but these types of flame retardants will have an impact on the environment.
[0005] CN107434838B discloses a phosphorus-containing olefin polymer, which synthesizes a phosphorus-containing cycloolefin copolymer by using cycloolefin and vinyl phosphorus-containing compound. Although the cycloolefin copolymer prepared by this method has good flame retardant properties, the polymer prepared by this method is a cross-linked product and cannot meet the requirements of optical applications. It is mainly used in the fields of self-adhesive copper foil, prepreg, laminate or printed circuit board.
[0006] TW202411410A discloses a phosphorus-containing composition, which is composed of a polymer formed by a plurality of cycloolefin monomers, an organic phosphorus compound, a crosslinking agent, a free radical initiator, a tackifier, and one or more suitable additives. The composition prepared by the method has good low dielectric constant, low loss characteristics, good thermal properties and flame retardancy. The phosphorus-containing composition prepared by the method, wherein the organic phosphorus compound is added to the polymer as an additive, is mainly used as an insulating material and is applied to electromechanical devices in various automotive parts.
[0007] The phosphorus-containing cycloolefin composition obtained by the prior art has improved flame retardancy, but its optical properties cannot meet the requirements of high-end applications. Therefore, the development of a flame retardant material with good flame retardancy and excellent optical properties is still a technical problem that needs to be urgently solved in this field. Summary of the invention
[0008] The first technical problem to be solved by the present invention is to provide a phosphorus-containing cycloolefin copolymer with good flame retardancy and excellent optical properties in view of the current status of the prior art.
[0009] The second technical problem to be solved by the present invention is to provide a method for preparing the above phosphorus-containing cycloolefin copolymer.
[0010] The third technical problem to be solved by the present invention is to provide an application of the above phosphorus-containing cycloolefin copolymer.
[0011] The technical solution adopted by the present invention to solve the first technical problem is: a phosphorus-containing cycloolefin copolymer, characterized by the general formula:
[0012] Formula I;
[0013] Wherein, R0 is a C1~C5 alkyl group;
[0014] R1, R2, R3, R4 are -H, C1~C 20 Straight or branched alkyl, C5~C 20 Cycloalkyl, C3~C6 alkoxy, C6~C 20 One of the aromatic groups;
[0015] R5, R6, R7, R8 are -H, halogen, C1~C 20 Straight or branched alkyl, C3~C 20 Cycloalkyl, C6~C 30 Aryl, C3~C 20 One of the heteroaryl groups;
[0016] a is a natural number, for example, it can be 0, 1, 2, 3, 4, etc.;
[0017] b is 0 or 1;
[0018] The molar ratio of x, y, and z is (1~10%):(55~99%):(0~35%).
[0019] Preferably, the molar ratio of the sum of x and z to y is (1-45):55.
[0020] Preferably, R1, R2, R3, and R4 are one of -H, C1-C3 straight or branched alkyl, C5-C7 cycloalkyl, C3-C6 alkoxy, and C6-C8 aryl;
[0021] The R5, R6, R7 and R8 are one of -H, C1-C5 straight chain or branched chain alkyl, C3-C6 cycloalkyl and C6-C8 aryl.
[0022] The technical solution adopted by the present invention to solve the second technical problem is: a method for preparing the above-mentioned phosphorus-containing cycloolefin copolymer, characterized by comprising the following steps: in a system with a water oxygen content of <1ppm, at a certain temperature and pressure, using cycloalkane or aromatic hydrocarbon as a solvent, a metallocene catalyst as a main catalyst, and an alkyl aluminum as a co-catalyst, polymerizing comonomer A, comonomer B and α-olefin to obtain the desired phosphorus-containing cycloolefin copolymer;
[0023] The general formula of the comonomer A is:
[0024] Formula II;
[0025] The general formula of the comonomer B is:
[0026] Formula III.
[0027] Preferably, the comonomer A is one of the following IIa~IId;
[0028] .
[0029] Preferably, the comonomer B is one of the following IIIa~IIId;
[0030] .
[0031] Preferably, the α-olefin is one of ethylene, propylene, butene and pentene, and more preferably ethylene.
[0032] Preferably, the metallocene catalyst is a metallocene compound of a transition metal such as titanium, zirconium, or hafnium, specifically ethoxydimethylsilyldi(4,5,6,7-tetrahydro-1-indenyl)diethyltitanium, dimethylsilyldi(4,5,6,7-tetrahydro-1-indenyl)titanium dichloride, dimethylsilyldi(4,5,6,1-tetrahydro-1-indenyl)titanium dibromide, dimethylsilyldi(4-methyl-1-indenyl)titanium dichloride, dimethylsilyldi( 2,3-dimethyl-1-indenyl) titanium, dimethylsilylenebis(4,1-dimethyl-1-indenyl) titanium dichloride, dimethylsilylenebis(4,1-dimethoxy-1-indenyl) titanium dichloride, diethylsilylenebis(fluorenyl) titanium dichloride, dimethylsilylenebis(fluorenyl) titanium dimethyl, zirconocene dichloride, methoxydimethylsilylenebis(indenyl) zirconium, dimethylsilylenebis(indenyl) zirconium chloride, dimethylsilylenebis(indenyl) methoxy zirconium chloride, Dimethylsilylenebis(indenyl)ethoxyzirconium chloride, dimethylsilylenebis(indenyl)methylzirconium chloride, dimethylsilylenebis(indenyl)zirconium dichloride, dimethylsilylenebis(indenyl)zirconium monochloride, dimethylsilylenebis(indenyl)zirconium diphenyl chloride, dimethylsilylenebis(fluorenyl)zirconium dichloride, dimethylsilylenebis(indenyl)ethoxyhafnium chloride, dimethylsilylenebis(indenyl)dimethylhafnium, dimethylsilylenebis(indenyl)diethylhafnium, At least one of methylsilylenebis(indenyl)dibenzyl hafnium, dimethylsilylenebis(indenyl)methyl hafnium monobromide, dimethylsilylenebis(indenyl)ethyl hafnium monobromide, dimethylsilylenebis(indenyl)benzyl hafnium monochloride, dimethylsilylenebis(indenyl)methyl hafnium monochloride, dimethylsilylenebis(fluorenyl)dimethyl hafnium, and dimethylsilylenebis(fluorenyl)diphenyl hafnium, more preferably dichlorodizirconocene or diethylsilylenebis(fluorenyl)titanium dichloride;
[0033] The alkyl aluminum co-catalyst is at least one of trimethyl aluminum, triethyl aluminum, tripropyl aluminum, triisopropyl aluminum, tri-n-butyl aluminum, triisobutyl aluminum, tri-sec-butyl aluminum, tri-tert-butyl aluminum, tripentylaluminum, trihexylaluminum, trioctylaluminum and tridecylaluminum, tricyclohexylaluminum, tricyclooctylaluminum, dimethylaluminum chloride, diethylaluminum chloride, diethylaluminum azide, diisobutylaluminum chloride, diethylaluminum hydride, diisobutylaluminum hydride, methylaluminumoxane, ethylaluminumoxane, methoxydimethylaluminum, ethoxydiethylaluminum and phenoxydiethylaluminum, and is more preferably triethylaluminum or methylaluminumoxane (MAO);
[0034] The solvent includes at least one of toluene, o-xylene, m-xylene, p-xylene, mesitylene, cyclopentane, methylcyclopentane, cyclohexane, methylcyclohexane, cycloheptane and cyclooctane, and more preferably methylcyclohexane or toluene.
[0035] Preferably, the reaction temperature of the polymerization reaction is 5-100° C., the reaction pressure is 1-50 bar, and the reaction time is 5-60 min. The reaction temperature is more preferably 10-40° C., the reaction pressure is more preferably 5-30 bar, and the reaction time is more preferably 10-30 min.
[0036] Preferably, the mass ratio of the sum of the comonomer A and the comonomer B to the solvent is (10-30):(70-90), more preferably (10-15):(85-90);
[0037] The molar ratio of the metallocene catalyst to the total of comonomer A and comonomer B is 1:(10 2 ~10 4 ), more preferably 1:(10 2 ~10 3 );
[0038] The molar ratio of the metal element in the metallocene catalyst to the metal Al in the alkyl aluminum catalyst is 1:(500-5000), and more preferably 1:(500-1000).
[0039] Preferably, the chain transfer agent of the polymerization reaction is at least one of hydrogen, dimethyl zinc, diethyl zinc, dipropyl zinc, and diisobutyl zinc, and more preferably hydrogen.
[0040] Preferably, the molar ratio of the chain transfer agent to the metallocene catalyst is (5-1000):1, more preferably (100-800):1.
[0041] The technical solution adopted by the present invention to solve the third technical problem is: an application of the above-mentioned phosphorus-containing cyclic olefin copolymer, characterized in that: the phosphorus-containing cyclic olefin copolymer is used in the preparation of high-end optical fireproof materials, high-transmittance fireproof medical materials, polarizer films, high-transmittance fire-fighting materials, and new energy battery films.
[0042] Compared with the prior art, the advantages of the present invention are that the phosphorus-containing cycloolefin copolymer prepared by the present invention has excellent flame retardancy, heat resistance and light transmittance, and can meet the current market demand. DETAILED DESCRIPTION
[0043] The present invention is further described in detail below with reference to the embodiments.
[0044] Embodiment 1:
[0045] In a 2.0L reactor, the pressure was 10 bar. The system was first repeatedly evacuated and replaced with nitrogen three times at 500°C, and then replaced with ethylene three times, maintaining an ethylene flow rate of 50NL / hr, so that the entire reaction system met the requirements of sealing, anhydrous and oxygen-free, and then the system temperature was set to 20°C;
[0046] Then, 80.9 g of the compound of formula IIa and 50.5 g of the compound of formula IIIa, 1530 ml of methylcyclohexane, and 11 ml of hydrogen were added to the system. The catalyst used was ZrCp2Cl2, and 68.52 ml of a solution with a concentration of 10 μmol / L was prepared with methylcyclohexane. The co-catalyst was triethylaluminum, and 82.23 ml of a solution with a molar ratio of zirconium to aluminum was prepared with methylcyclohexane. After reacting for 20 minutes, 2 ml of methanol was injected to terminate the reaction.
[0047] Subsequently, a 10 wt% NaOH aqueous solution of 2 / 5 of the polymer solution was added, and the mixture was stirred and washed in a water bath at 70°C for 2 hours. The polymer solution was then washed with pure water until neutral, and the polymer was precipitated with more than three times ethanol to obtain the polymer. The polymer was vacuum dried at 120°C for more than 8 hours to obtain 106.00 g of copolymer.
[0048] Embodiment 2:
[0049] The difference from Example 1 is that: 55.8g of the compound with structure IIa and 40g of the compound with structure IIIa are used as comonomers; the catalyst used is ZrCp2Cl2, which is prepared into a solution with a concentration of 10μmol / L with methylcyclohexane and 53.11ml is taken; the co-catalyst is triethylaluminum, which is prepared into a solution with a concentration of 5mol / L with methylcyclohexane and 63.73ml is taken; the solvent is 1119ml methylcyclohexane; the hydrogen is 8.5ml; and 81.35g of copolymer is obtained after post-polymerization treatment.
[0050] Embodiment 3:
[0051] The difference from Example 1 is that: 40.3g of the compound with structure IIa and 40g of the compound with structure IIIa are used as comonomers; the catalyst used is ZrCp2Cl2, which is prepared into a solution with a concentration of 10μmol / L with methylcyclohexane and 49.98ml is taken; the co-catalyst is triethylaluminum, which is prepared into a solution with a concentration of 5mol / L with methylcyclohexane and 59.98ml is taken; the solvent is 938ml of methylcyclohexane; the hydrogen is 8.0ml; and 66.63g of copolymer is obtained after post-polymerization treatment.
[0052] Embodiment 4:
[0053] The difference from Example 1 is that: 35.1g of the compound with structure IIb and 40g of the compound with structure IIIa are used as comonomers; the catalyst used is ZrCp2Cl2, which is prepared into a solution with a concentration of 10μmol / L with methylcyclohexane and 49.09ml is taken; the co-catalyst is triethylaluminum, which is prepared into a solution with a concentration of 5mol / L with methylcyclohexane and 58.91ml is taken; the solvent is 877ml of methylcyclohexane; the hydrogen is 8.0ml; and 65.70g of copolymer is obtained after post-polymerization treatment.
[0054] Embodiment 5:
[0055] The difference from Example 1 is that: 68.3g of the compound with structure IIb and 40g of the compound with structure IIIa are used as comonomers; the catalyst used is ZrCp2Cl2, which is prepared into a solution with a concentration of 10μmol / L with methylcyclohexane and 54.82ml is taken; the co-catalyst is triethylaluminum, which is prepared into a solution with a concentration of 5mol / L with methylcyclohexane and 65.78ml is taken; the solvent is 1266ml of methylcyclohexane; the hydrogen is 8.5ml; and 96.36g of copolymer is obtained after post-polymerization treatment.
[0056] Embodiment 6:
[0057] The difference from Example 1 is that: 58.8g of the compound with structure IIb and 40g of the compound with structure IIIa are used as comonomers; the catalyst used is ZrCp2Cl2, which is prepared into a solution with a concentration of 10μmol / L with methylcyclohexane and 53.11ml is taken; the co-catalyst is triethylaluminum, which is prepared into a solution with a concentration of 5mol / L with methylcyclohexane and 63.73ml is taken; the solvent is 1155ml of methylcyclohexane; the hydrogen is 8.5ml; and 85.95g of copolymer is obtained after post-polymerization treatment.
[0058] Embodiment 7:
[0059] The difference from Example 1 is that: 30.4g of the compound with structure IIb and 40g of the compound with structure IIIa are used as comonomers; the catalyst used is ZrCp2Cl2, which is prepared into a solution with a concentration of 10μmol / L with methylcyclohexane and 30.49ml is taken; the co-catalyst is triethylaluminum, which is prepared into a solution with a concentration of 5mol / L with methylcyclohexane and 36.59ml is taken; the solvent is 823ml of methylcyclohexane; the hydrogen is 5.0ml; and 57.71g of copolymer is obtained after post-polymerization treatment.
[0060] Embodiment 8:
[0061] The difference from Example 1 is that: 24.5g of the compound with structure IIb and 40g of the compound with structure IIIb are used as comonomers; the catalyst used is ZrCp2Cl2, which is prepared into a solution with a concentration of 10μmol / L with methylcyclohexane and 29.41ml is taken; the co-catalyst is triethylaluminum, which is prepared into a solution with a concentration of 5mol / L with methylcyclohexane and 35.29ml is taken; the solvent is 753ml of methylcyclohexane; the hydrogen is 4.5ml; and 56.05g of copolymer is obtained after post-polymerization treatment.
[0062] Embodiment 9:
[0063] The difference from Example 1 is that: 7.9g of the compound with structure IIb and 40g of the compound with structure IIIb are used as comonomers; the catalyst used is ZrCp2Cl2, which is prepared into a solution with a concentration of 10μmol / L with methylcyclohexane and 26.32ml is taken; the co-catalyst is triethylaluminum, which is prepared into a solution with a concentration of 5mol / L with methylcyclohexane and 31.58ml is taken; the solvent is 560ml methylcyclohexane; the hydrogen is 4.0ml; and 38.30g of copolymer is obtained after post-polymerization treatment.
[0064] Embodiment 10:
[0065] The difference from Example 1 is that: 32.6g of the compound with structure IIc and 40g of the compound with structure IIIb are used as comonomers; the catalyst used is ZrCp2Cl2, which is prepared into a solution with a concentration of 10μmol / L with methylcyclohexane and 28.74ml is taken; the co-catalyst is triethylaluminum, which is prepared into a solution with a concentration of 5mol / L with methylcyclohexane and 34.48ml is taken; the solvent is 849ml of methylcyclohexane; the hydrogen is 4.5ml; and 63.85g of copolymer is obtained after post-polymerization treatment.
[0066] Embodiment 11:
[0067] The difference from Example 1 is that: 23.0g of the compound with structure IIc and 40g of the compound with structure IIIc are used as comonomers; the catalyst used is ZrCp2Cl2, which is prepared into a solution with a concentration of 10μmol / L with methylcyclohexane and 27.05ml is taken; the co-catalyst is triethylaluminum, which is prepared into a solution with a concentration of 5mol / L with methylcyclohexane and 32.45ml is taken; the solvent is 736ml of methylcyclohexane; the hydrogen is 4.0ml; and 56.68g of copolymer is obtained after post-polymerization treatment.
[0068] Embodiment 12:
[0069] The difference from Example 1 is that: 14.5g of the compound with structure IIc and 40g of the compound with structure IIIc are used as comonomers; the catalyst used is ZrCp2Cl2, which is prepared into a solution with a concentration of 10μmol / L with methylcyclohexane and 25.54ml is taken; the co-catalyst is triethylaluminum, which is prepared into a solution with a concentration of 5mol / L with methylcyclohexane and 30.65ml is taken; the solvent is 637ml of methylcyclohexane; the hydrogen is 4.0ml; and 46.30g of copolymer is obtained after post-polymerization treatment.
[0070] Embodiment 13:
[0071] The difference from Example 1 is that: 40g of the compound with structure IIa is used as the comonomer; the catalyst used is ZrCp2Cl2, which is prepared into a solution with a concentration of 10μmol / L with methylcyclohexane and 7.63ml is taken; the co-catalyst is triethylaluminum, which is prepared into a solution with a concentration of 5mol / L with methylcyclohexane and 9.15ml is taken; the solvent is 468ml of methylcyclohexane; the hydrogen is 1.5ml; and 34.40g of copolymer is obtained after post-polymerization treatment.
[0072] Comparative Example 1:
[0073] The difference from Example 1 is that: 20g of formula IIIa is used as the comonomer; the catalyst used is ZrCp2Cl2, which is prepared into a 10μmol / L solution in methylcyclohexane and 21.24ml is taken; the co-catalyst is triethylaluminum, which is prepared into a 5mol / L solution in methylcyclohexane and 25.49ml is taken; the solvent is 234ml methylcyclohexane; the hydrogen is 3.5ml; and 18.60g of copolymer is obtained after post-polymerization treatment.
[0074] Comparative Example 2:
[0075] The difference from Example 1 is that: 15g of formula IIIa and 47.62g of formula IIIb structural compounds are used as comonomers; the catalyst used is ZrCp2Cl2, which is prepared into a 10μmol / L solution with methylcyclohexane and 45.52ml is taken; the co-catalyst is triethylaluminum, which is prepared into a 5mol / L solution with methylcyclohexane and 54.62ml is taken; the solvent is 732ml of methylcyclohexane; the hydrogen is 7.5ml; and after post-polymerization treatment, 55.48g of copolymer is obtained.
[0076] The performance test results of the copolymers prepared in all the above embodiments and comparative examples are shown in Table 1.
[0077] Table 1:
[0078]
[0079] The specific test steps are as follows:
[0080] (1) x, y, z: The structure of the prepared polymer was determined using a nuclear magnetic resonance spectrometer (NMR, Bruker 400 MHz, Bruker, Switzerland) at 25 °C with deuterated chloroform (CDCl3) as solvent and tetramethylsilane (TMS) as internal standard;
[0081] (2) Glass transition temperature: Take 5.0-7.0 mg of polymer sample, heat it to 260°C at 40°C / min, keep it constant for 5 min to eliminate thermal history, then cool it to 40°C at 20°C / min, keep it constant for 5 min, and then heat it to 260°C at 20°C / min. The glass transition temperature of the polymer is obtained from the second heating curve.
[0082] (3) Flame retardant level: Refer to GB / T 2408-2008 for the determination of the combustion level, and use the horizontal and vertical combustion test methods for determination;
[0083] (4) Light transmittance: The polymer was molded into a disc with a diameter of 25 mm and a thickness of 1 mm, and the light transmittance was measured under a standard C light source with a wavelength of 380-780 nm.
[0084] From Table 1 we can see that:
[0085] (1) The present invention uses comonomer A (a compound having a structure shown in formula II), comonomer B (a compound having a structure shown in formula III) and α-olefin for copolymerization, which can effectively improve the flame retardancy, heat resistance and light transmittance of the prepared cycloolefin copolymer, and can improve the flame retardancy grade of the cycloolefin copolymer from HB to V2 or V1;
[0086] Patent CN107434838B loses its original linear structure due to the limitation of polymerization conditions, thus reducing the optical performance. Patent TW202411410A mainly acts on insulating materials, adding a large amount of cross-linking agents and tackifiers to improve its insulation and flame retardancy, but at the expense of optical performance. However, the polymer obtained by polymerization in the present invention is a linear polymer due to the different polymerization mechanism, without cross-linking or other additives that affect the optical performance, and retains the optical properties of cycloolefin copolymers.
[0087] (2) By comparing Example 1 and Example 13, it can be seen that when the amount of comonomer B added is 0, the flame retardancy of the cycloolefin copolymer obtained by copolymerization can also reach V1;
[0088] (3) Compared with Example 1, the flame retardancy grade of the cycloolefin copolymers provided in Comparative Examples 1 and 2 is HB, and the flame retardancy is relatively low.
Claims
1. A phosphorus-containing cycloolefin copolymer, characterized in that The general formula is: Formula I; Wherein, R0 is a C1~C5 alkyl group; R1, R2, R3, R4 are -H, C1~C 20 Straight or branched alkyl, C5~C 20 Cycloalkyl, C3~C6 alkoxy, C6~C 20 One of the aromatic groups; R5, R6, R7, R8 are -H, halogen, C1~C 20 Straight or branched alkyl, C3~C 20 Cycloalkyl, C6~C 30 Aryl, C3~C 20 One of the heteroaryl groups; a is a natural number; b is 0 or 1; The molar ratio of x, y, and z is (1~10%):(55~99%):(0~35%).
2. The phosphorus-containing cyclic olefin copolymer according to claim 1, characterized in that: The molar ratio of the sum of x and z to y is (1~45):
55.
3. The phosphorus-containing cyclic olefin copolymer according to claim 1, characterized in that: The R1, R2, R3, and R4 are one of -H, C1-C3 straight or branched alkyl, C5-C7 cycloalkyl, C3-C6 alkoxy, and C6-C8 aryl; The R5, R6, R7 and R8 are one of -H, C1-C5 straight chain or branched chain alkyl, C3-C6 cycloalkyl and C6-C8 aryl.
4. A method for preparing the phosphorus-containing cycloolefin copolymer according to any one of claims 1 to 3, characterized in that The method comprises the following steps: in a system with a water oxygen content of less than 1 ppm, at a certain temperature and pressure, using cycloalkane or aromatic hydrocarbon as a solvent, a metallocene catalyst as a main catalyst, and an alkyl aluminum as a cocatalyst, polymerizing comonomer A, comonomer B and ethylene to obtain a desired phosphorus-containing cycloolefin copolymer; The general formula of the comonomer A is: Formula II; The general formula of the comonomer B is: Formula III.
5. The preparation method according to claim 4, characterized in that: The comonomer A is one of the following IIa~IId; 。 6. The preparation method according to claim 4, characterized in that: The comonomer B is one of the following IIIa~IIId; 。 7. The preparation method according to claim 4, characterized in that: The metallocene catalyst is ethoxydimethylsilylenebis(4,5,6,7-tetrahydro-1-indenyl)diethyltitanium, dimethylsilylenebis(4,5,6,7-tetrahydro-1-indenyl)titanium dichloride, dimethylsilylenebis(4,5,6,1-tetrahydro-1-indenyl)titanium dibromide, dimethylsilylenebis(4-methyl-1-indenyl)titanium dichloride, dimethylsilylenebis(2,3-dimethyl-1-indenyl)titanium dichloride. dichlorodimethylsilylenebis(4,1-dimethyl-1-indenyl)titanium, dichlorodimethylsilylenebis(4,1-dimethoxy-1-indenyl)titanium, dichlorodiethylsilylenebis(fluorenyl)titanium, dichlorodimethylsilylenebis(fluorenyl)titanium, dichlorodimethylzirconocene, methoxydimethylsilylenebis(indenyl)zirconium, dichlorodimethylsilylenebis(indenyl)zirconium, dichlorodimethylsilylenebis(indenyl)zirconium, dichlorodimethylsilylenebis(indenyl)zirconium, Zirconium dimethylsilylenebis(indenyl)ethoxyzirconium chloride, dimethylsilylenebis(indenyl)methylzirconium chloride, dimethylsilylenebis(indenyl)zirconium dichloride, dimethylsilylenebis(indenyl)zirconium monochloride, dimethylsilylenebis(indenyl)zirconium monohydride, dimethylsilylenebis(fluorenyl)diphenylzirconium, dimethylsilylenebis(fluorenyl)zirconium dichloride, dimethylsilylenebis(indenyl)ethoxyhafnium chloride, dimethylsilylenebis(indenyl)dimethylhafnium, dimethyl at least one of dimethylsilylenebis(indenyl)diethyl hafnium, dimethylsilylenebis(indenyl)dibenzyl hafnium, dimethylsilylenebis(indenyl)methyl hafnium monobromide, dimethylsilylenebis(indenyl)ethyl hafnium monobromide, dimethylsilylenebis(indenyl)benzyl hafnium monochloride, dimethylsilylenebis(indenyl)methyl hafnium monochloride, dimethylsilylenebis(fluorenyl)dimethyl hafnium, and dimethylsilylenebis(fluorenyl)diphenyl hafnium; The alkyl aluminum co-catalyst is at least one of trimethyl aluminum, triethyl aluminum, tripropyl aluminum, triisopropyl aluminum, tri-n-butyl aluminum, triisobutyl aluminum, tri-sec-butyl aluminum, tri-tert-butyl aluminum, tripentylaluminum, trihexylaluminum, trioctylaluminum and tridecylaluminum, tricyclohexylaluminum, tricyclooctylaluminum, dimethylaluminum chloride, diethylaluminum chloride, diisobutylaluminum chloride, diethylaluminum hydride, diisobutylaluminum hydride, methylaluminumoxane, ethylaluminumoxane, methoxydimethylaluminum, ethoxydiethylaluminum and phenoxydiethylaluminum; The solvent includes at least one of toluene, o-xylene, m-xylene, p-xylene, mesitylene, cyclopentane, methylcyclopentane, cyclohexane, methylcyclohexane, cycloheptane and cyclooctane.
8. The preparation method according to claim 4, characterized in that: The polymerization reaction has a reaction temperature of 5-100° C., a reaction pressure of 1-50 bar, and a reaction time of 5-60 min.
9. The preparation method according to claim 4, characterized in that: The mass ratio of the sum of the comonomer A and the comonomer B to the solvent is (10-30):(70-90); The molar ratio of the metallocene catalyst to the total of comonomer A and comonomer B is 1:(10 2 ~10 4 ); The molar ratio of the metal element in the metallocene catalyst to the metal Al in the alkyl aluminum catalyst is 1:(500-5000).
10. Use of the phosphorus-containing cyclic olefin copolymer according to any one of claims 1 to 3, characterized in that: The phosphorus-containing cyclic olefin copolymer is used in the preparation of high-end optical fireproof materials, high-transmittance fireproof medical materials, polarizer films, high-transmittance fire-fighting materials, and new energy battery films.
Citation Information
Patent Citations
Phosphorus-containing olefin polymers, their preparation methods, their compositions and finished products
CN107434838B
Flame retardant compositions containing polycyclic-olefinic polymer with olefinic functionality for forming low-loss films having improved dielectric and thermal properties
TW202411410A
Block copolymer of polyolefine and phosphorus-containing alkene and preparation method thereof
CN102757542A
Polymerizable composition, cycloolefin-based polymer, cycloolefin-based resin molded body, and laminate
CN104995232A